Infants of Mothers With Diabetes and Subsequent Attention Deficit Hyperactivity Disorder: A Retrospective Cohort Study - Lin, Chien-Heng; Lin, Wei-De; Chou, I-Ching; Lee, Inn-Chi; Hong, Syuan-Yu (Frontiers in Pediatrics, 2019)
Background: Maternal diabetes mellitus (DM) increases the risk of fetal, neonatal, and long-term complications in offspring. Although this has been widely known for decades, data are limited regarding the effect of maternal pregestational and gestational diabetes on the subsequent neurodevelopmental outcome of offspring. This study investigated whether infants of mothers with diabetes (IDMs) were associated with a risk of subsequent attention deficit hyperactivity disorder (ADHD). Objectives: We collected data from newborn infants born to mothers with gestational or pregestational diabetes at China Medical University Children’s Hospital between January 1, 2006, and December 31, 2012. These patients were followed to evaluate their risk of ADHD (IDM group) compared with that for those born to mothers without DM(non-IDM group). Several assumed perinatal risk factors accompanying the IDMs were also analyzed. Results: Overall, 104 patients with average gestational ages of 36.5 weeks were included in the IDM group. Additionally, 110 patients with average gestational ages of 36.6 weeks were included in the non-IDM group. Compared with non-IDMs (reference), the overall risk of ADHD in IDMs was 2.6 (95% confidence interval [CI], 1.11–5.90; p = 0.03). Furthermore, the risk of ADHD among male (OR, 3.78; 95% CI, 1.37–10.3; p = 0.001) and full-term infants (odds ratio [OR], 4.5; 95% CI, 1.16–17.6; p = 0.03) in the IDMs was higher than that in the non-IDM group. No significant differences were found among IDMs for the assumed perinatal risk factors that were analyzed. Conclusions: The study revealed a higher incidence rate of ADHD in IDMs, especially male and full-term infants. It is crucial for pediatricians to identify the early symptoms neurodevelopmental disorders, especially ADHD, in children of diabetic mothers to initiate proper assessment and treatment.